DETERMINAN FAKTOR PERKAWINAN ANAK (STUDI KASUS KECAMATAN LIMBOTO KABUPATEN GORONTALO) - AMALIA, LIA (Tadulako University, 2024)
Child marriage refers to the intimate union of a man and women under 19 years of age as a legal family. Gorontalo province is ranked the 15th with child marriage cases, particulary in a women with a percentage 0f 13,20%. The figure is eight times higher than the national standar, which is 10,82% (statistics Indonesia, 2020). Problem statement in this research is how the description of determinant of child marriage in Limboto Subdistrict, Gorontalo District. This research aims at gaining a description of the determinant of child marriage in Limboto Subdistrict, Gorontalo District. This type of research is a descriptive survey with a population of 219 married women aged <19 years and a sample of 142 people using purposive sampling and univariate data analysis. The results show that out of 142 respondents, 95 respondents (66.9%) have a sufficient level of knowledge about child marriage, 86 respondents (60.6%) have positive support for child marriage, 130 respondents (91.5%) have low economic status of their parents. , 84 respondents (59.2%) received an authoritarian parenting style from their parents, 77 respondents (54.2%) had peers who played a significant role in their marriage, most of the father's work was a farmer, 50 respondents (35.2%) ) and the mother's most common type of work was a housewife, 101 respondents (71.1).. It is hoped that parents will be the most comfortable place for children to complain about whatever problems they face, whether at school or in their circle of friends, and that teenagers will be more active in seeking information regarding the impact of child marriage on reproductive health and can sort out their relationships so that they remain in the circle of good social relations. Keywords: Child; Determinants; Women; Marriage